Double Trap Interface: A novel gas interface for high throughput analysis of biomedical samples by AMS. (August 2021) - De Maria, Daniele; Fahrni, Simon M.; Lozac'h, Frédéric; Marvalin, Cyrille; Walles, Markus; Camenisch, Gian; Wacker, Lukas; Synal, Hans-Arno
Abstract: Although Accelerator Mass Spectrometry (AMS) offers unparalleled sensitivity by investigating the fate of 14 C-labeled compounds within the organism, its widespread use in ADME (absorption, distribution, metabolism, excretion) studies is limited. Conventional approaches based on Liquid Scintillation Counting (LSC) are still preferred, in particular because of complexity and costs associated with AMS measurements. Progress made over the last decade towards more compact AMS systems increased the interest in a combustion-based AMS approach allowing the analysis of samples in gaseous form. Thus, a novel gas Double Trap Interface (DTI) was designed, providing high sample throughput for the analysis of biomedical samples. DTI allows the coupling of an Elemental Analyzer (EA) for sample combustion to the hybrid ion source of a MICADAS (MIni CArbon DAting System) AMS system. The performance was evaluated in two studies through the analysis of more than 1000 samples from 14 C-labeled biomatrices and fractions collected after liquid chromatography (LC). The covered activity ranged from 1 to 1000 mBq/g for labeled biomatrices and from 1 to 10000 mBq/g(C) for LC fractions. The implemented routine allows automated measurements requiring less than 5 min per sample (12–13 analyses per hour) without the need for sample conversion to graphite.